International Differences in the Links between Obesity and Physiological Dysregulation: The United States, England, and Taiwan. (28th May 2013) - Vasunilashorn, Sarinnapha; Kim, Jung Ki; Crimmins, Eileen M.
Abstract : Excess weight has generally been associated with adverse health outcomes; however, the link between overweight and health outcomes may vary with socioeconomic, cultural, and epidemiological conditions. We examine associations of weight with indicators of biological risk in three nationally representative populations: the US National Health and Nutrition Examination Survey, the English Longitudinal Study of Ageing, and the Social Environment and Biomarkers of Aging Study in Taiwan. Indicators of biological risk were compared for obese (defined using body mass index (BMI) and waist circumference) and normal weight individuals aged 54+. Generally, obesity in England was associated with elevated risk for more markers examined; obese Americans also had elevated risks except that they did not have elevated blood pressure (BP). Including waist circumference in our consideration of BMI indicated different links between obesity and waist size across countries; we found higher physiological dysregulation among those with high waist but normal BMI compared to those with normal waist and normal BMI. Americans had the highest levels of biological risk in all weight/waist groups. Cross-country variation in biological risk associated with obesity may reflect differences in health behaviors, lifestyle, medication use, and culture.